Melodramatic Music in the Western - Whitmer, Mariana (Journal of Film Music, 2013)
The Western film developed from a variety of sources, including written and visual sources, such as the classic and dime novels, as well as paintings and photographs. Eventually these were dramatized with live action in the rodeo, Wild West shows, and on stage, particularly in melodramas. In his history of the Western film, David Lusted points out, “Whether gunfighter or outlaw criminal, cowboy or sheriff, the Western hero is invariably a romantic hero of melodrama.” The Western owes a great deal to melodrama, not the least of which is the music that usually accompanies it. Owing to the substantial amount of action and infrequent dialogue, Westerns particularly rely on music to convey excitement, tension, and all the other emotions so necessary to their popularity. As exhibited in the collections of photoplay music and silent film cue sheets, the Western film score appropriated many of the musical clichés that accompanied the staged works of the late nineteenth century. This presentation will begin to trace the history of the music that accompanied the Western narrative from the stage to the screen, demonstrating how many of the aural clues that enhance our enjoyment of this genre today have their roots in late nineteenth century melodrama.